PENGARUH DANA PIHAK KETIGA, PEMBIAYAAN MUDHARABAH, DAN NPF TERHADAP LABA BERSIH BANK UMUM SYARIAH DI INDONESIA - Dzakwan, Rifqi; Nugroho Suryo Bintoro (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Sharia banking measures the success of a company's performance using one important indicator, namely profit, increasing profits indicate better performance of sharia banking. Therefore, the aim of this research is to analyze factors that can influence profits at Islamic commercial banks in Indonesia, including third party funds, mudharabah financing, and non-performance financing. This research uses a quantitative approach, with secondary data obtained from the Financial Services Authority. This research was carried out using the multiple linear regression analysis method which aims to determine the influence of the independent variable on the dependent variable. Based on the research results, all independent variables, namely Third Party Funds, Mudharabah Financing, and Non-Performing Financing simultaneously have a significant influence on the dependent variable net profit. Based on the partial test, it shows that the Third Party Funds variable has a significant positive effect on net profit and Non-Performing Financing has a significant negative effect on net profit, while the Mudharabah Financing variable has no significant effect on net profit at Islamic commercial banks in Indonesia.